Implementation of Tuberculosis Financing Policies: A Case Study of Solok District, Indonesia - Tuty Ernawati; Luthfil Hadi Anshari (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Tuberculosis (TB) remains a global health priority aligned with the 2030 Sustainable Development Goals (SDGs). However, financing challenges persist in many districts and cities across Indonesia, including West Sumatra Province. Funding for TB programs still relies heavily on external sources, particularly the Global Fund (GF), while local health budgets remain minimal, covering only 0.05–0.1% of total health expenditures. This study aimed to identify the key problems in TB financing policies at the district level. A descriptive qualitative design with a case study approach was employed, involving seven informants from the District Health Office and two community health centers (puskesmas) with the highest TB cases, selected through purposive sampling. Findings revealed that limited and fragmented financing has hindered the implementation of TB services and the achievement of Minimum Service Standards for TB suspect management. Contributing factors include a shortage of skilled human resources for recording and reporting, inadequate infrastructure, and insufficient operational funds across programs. These constraints have reduced the quality and coverage of TB examination and treatment services. Weak local government commitment to prioritizing TB programs has further slowed progress toward achieving national targets as set by Presidential Regulation No. 67 of 2021, which aims to reduce TB mortality to 6 per 100,000 and incidence to 65 per 100,000 by 2030. To strengthen policy implementation, the District Health Office must establish and ratify standardized TB referral flows and ensure adequate budget allocations. Furthermore, these financing standards and guidelines need to be effectively disseminated across the entire community health center network.